Acute Heart Failure After Reperfused Ischemic Stroke: Association With Systemic and Cardiac Inflammatory Responses - Vornholz, Lilian; Nienhaus, Fabian; Gliem, Michael; Alter, Christina; Henning, Carina; Lang, Alexander; Ezzahoini, Hakima; Wolff, Georg; Clasen, Lukas; Rassaf, Tienush; Flögel, Ulrich; Kelm, Malte; et al. (Frontiers in Physiology, 2021)
Patients with acute ischemic stroke (AIS) present an increased incidence of systemic inflammatory response syndrome and release of Troponin T coinciding with cardiac dysfunction. The nature of the cardiocirculatory alterations remains obscure as models to investigate systemic interferences of the brain-heart-axis following AIS are sparse. Thus, this study aims to investigate acute cardiocirculatory dysfunction and myocardial injury in mice after reperfused AIS. Ischemic stroke was induced in mice by transient right-sided middle cerebral artery occlusion (tMCAO). Cardiac effects were investigated by electrocardiograms, 3D-echocardiography, magnetic resonance imaging (MRI), invasive conductance catheter measurements, histology, flow-cytometry and determination of high-sensitive Troponin T (hsTnT). Systemic hemodynamics were recorded and catecholamines and inflammatory markers in circulating blood and myocardial tissue were determined by immuno-assay and flow-cytometry.Twenty-four hours following tMCAO hsTnT was elevated 4-fold compared to controls and predicted long-term survival. In parallel, systolic left ventricular dysfunction occurred with impaired global longitudinal strain, lower blood pressure, reduced stroke volume and severe bradycardia leading to reduced cardiac output. This was accompanied by a systemic inflammatory response characterized by granulocytosis, lymphopenia, and increased levels of serum-amyloid P and interleukin-6. Within myocardial tissue, MRI relaxometry indicated expansion of extracellular space, most likely due to inflammatory edema and a reduced fluid volume. Accordingly, we found an increased abundance of granulocytes, apoptotic cells, and upregulation of pro-inflammatory cytokines within myocardial tissue following tMCAO. Therefore, reperfused ischemic stroke leads to specific cardiocirculatory alterations that are characterized by acute heart failure with reduced stroke volume, bradycardia, changes in cardiac tissue and accompanied by systemic and local inflammatory responses.